2023
DOI: 10.1186/s12955-023-02111-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and mental health measurements among patients with type 2 diabetes mellitus: a systematic review

Abstract: Background Over the past few decades the benefits of assessing Quality of Life (QoL) and mental health in patients with Type 2 Diabetes Mellitus (T2DM) have steadily increased with limited studies relating to the most useful method to assess these patients. This study aims to identify, review, summarise, and evaluate the methodological quality for the most validated commonly used health-related QoL and mental health assessment measurements in diabetic patients. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
1
0
0
Order By: Relevance
“…In both univariable and multivariable models, sex, BMI, and the presence of CVD and CKD showed notable associations with changes in RP. Consistent with our research, prior cross-sectional studies have similarly emphasized that sex, BMI, and sufficient physical activity are significant factors associated with PCS [ 32 34 ]. A study from Stanford also showed that in diabetics, the presence of obesity significantly impairs HRQoL [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…In both univariable and multivariable models, sex, BMI, and the presence of CVD and CKD showed notable associations with changes in RP. Consistent with our research, prior cross-sectional studies have similarly emphasized that sex, BMI, and sufficient physical activity are significant factors associated with PCS [ 32 34 ]. A study from Stanford also showed that in diabetics, the presence of obesity significantly impairs HRQoL [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with mental health problems may need additional support, including frequent medical consultations to manage their psychological conditions and diabetes. Moreover, mental health problems can increase the perception of symptom severity, leading to greater utilization of healthcare services (30,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Estas complicaciones, que varían desde alteraciones microvasculares, como la retinopatía diabética y la nefropatía, hasta macrovasculares, como enfermedades cardiovasculares y arteriales periféricas, representan un desafío considerable en el manejo clínico de la DM2 (Yapanis et al, 2022). Además, la carga emocional y psicológica asociada con la DM2, exacerbada por estas complicaciones, puede llevar a trastornos del ánimo, como la depresión y la ansiedad (Alzahrani et al, 2023).…”
Section: Introductionunclassified